2019
DOI: 10.1093/fampra/cmz089
|View full text |Cite
|
Sign up to set email alerts
|

Preventing unwanted situations and gaining trust: a qualitative study of older people and families’ experiences with advance care planning in the daily practice of primary care

Abstract: Background Using advance care planning (ACP) to anticipate future decisions can increase compliance with people’s end-of-life wishes, decrease inappropriate life-sustaining treatment and reduce stress, anxiety and depression. Despite this, only a minority of older people engage in ACP, partly because care professionals lack knowledge of approaches towards ACP with older people and their families. Objective To explore older pe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
32
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(33 citation statements)
references
References 27 publications
0
32
0
1
Order By: Relevance
“…Those studies were rated as moderate quality because the researcher’s theoretical and cultural orientations and potential influence are not mentioned in the research 31 51–53. Other studies were rated low-quality because they lacked study objectives, clearly stated data collection and analysis procedures, and participant ethical review guidelines 29 30 54 55…”
Section: Resultsmentioning
confidence: 99%
“…Those studies were rated as moderate quality because the researcher’s theoretical and cultural orientations and potential influence are not mentioned in the research 31 51–53. Other studies were rated low-quality because they lacked study objectives, clearly stated data collection and analysis procedures, and participant ethical review guidelines 29 30 54 55…”
Section: Resultsmentioning
confidence: 99%
“…Future studies should explore this rise and fall of trust and the relation with ACP more deeply. Other studies indicate a complex interaction between trust and ACP [10,[13][14][15]22].…”
Section: Discussionmentioning
confidence: 97%
“…In the Netherlands, 10% of the people aged 61 years or older have a living will [9]. In a recent study [10], a lack of trust or negative previous experiences with ACP could be a reason for older people not wanting to participate in ACP conversations; however, older people who did engage in ACP felt they could trust their GP more afterwards.…”
Section: Introductionmentioning
confidence: 99%
“…Reasons for having doubts in the current study could concern the willingness of others (the physician or a relative) to cooperate in their euthanasia request. Concerning the cooperation of the physician, previous studies have shown that negative euthanasia experiences in the family cause concern when it comes to patient’s own euthanasia wishes, or cause patients to not communicate with their physician about their own wishes at all [ 10 , 17 ]. This is in line with our finding that one of the participants explained that she thought it wasn’t going to be easy to get her wish for euthanasia carried out, because that is what she experienced with a family member.…”
Section: Discussionmentioning
confidence: 99%